Optimisation of transformation system and expression of a cinnamate-4-hydroxylase (C4H) gene silencing construct in suspension cells of boesenbergia rotunda / Wong Sher Ming - Wong, Sher Ming (2016)
Boesenbergia rotunda (L.) Mansf. also known as the fingerroot ginger or “Temu kunci” in Malay, produces valuable pharmaceutical compounds including panduratin A, 4’-hydroxypanduratin A, pinostrobin, pinocembrin chalcone, pinocembrin, isopanduratin A and cardamonin. In this study, an enzyme involved in the pathway responsible for biosynthesis of these compounds, cinnamate-4-hydroxylase (C4H) was partially cloned and a double-stranded RNA (dsRNA) construct was introduced for knockdown/ RNAi of the enzyme expression in B. rotunda cell suspension culture. Prior to the RNAi of the enzyme, a B. rotunda cell suspension culture and Agrobacterium-mediated transformation system was developed and optimised. The highest specific growth rate of the cell suspension was recorded as 0.0892±0.0035 in Murashige and Skoog liquid media supplemented with 1.0 mg L−1 of 2,4-dichlorophenoxyacetic acid and 0.5 mg L−1 6-benzyladenine, representing a 12-fold increase in cell volume during the culture period. Parameters affecting Agrobacterium-mediated transformation of the cell i.e. selection agent (hygromycin B) doses, co-cultivation periods and infection times were assessed. Optimal transformation efficiency was achieved when B. rotunda suspension cells were infected with Agrobacterium tumefaciens harbouring pCAMBIA1304 for 10 min and co-cultivated for 2 days. Polymerase Chain Reaction (PCR) and Southern hybridization analysis revealed stable integration of mgfp5 gene in the cell suspension culture up to 12-mo of maintenance and subculture. Out of 66 cell lines transformed with Agrobacterium carrying the C4H-dsRNA RNAi vector screened via PCR analysis, one cell line was obtained and Southern analysis confirmed the presence of gusl gene that functions as a hairpin loop in the RNAi vector. Quantitative-Reverse transcription PCR (qRT-PCR) analysis revealed the expression level of C4H transcripts in the RNAi cell line was 2-fold lower than wild type cells. The presence of homologous small RNAs in northern blot analysis but absence in the wild type confirmed that the knockdown was triggered by the dsRNA introduced. Differential expression of primary and secondary metabolites profiles were revealed via Liquid Chromatography Mass Spectrum (LC-MS) analysis. In conclusion, RNAi of the enzyme C4H via a partial hairpin dsRNA has provided insights into the functions and channels in the biosynthesis pathway involving the enzyme C4H which shown in this study, is non-redundant in biosynthesis of secondary metabolites in B. rotunda cell suspension. B. rotunda cell suspension could serve as a good system for secondary metabolite pathway study as well as compound production.